Development, preparation and safety testing of a Clostridium welchii Type C toxoid. II. Laboratory evaluation of potency - Knight, P.A.; Lucken, R.N.; Foster, W.; Walker, P.D. (Journal of biological standardization, 1979)
The results obtained with four laboratory tests on four candidate formulations of Clostridium welchii Type C vaccine for use in man have been compared with clinical responses to the same vaccines. Quantal response assays in mice appeared to reflect the ranking of the four vaccines in human subjects better than did the guinea pig tests. They also enabled the potency of the vaccine preparations to be related to an existing International Reference Preparation. Mouse assays in which the animals received two spaced doses of vaccine prior to challenge yielded marginally more satisfactory results in terms of precision and reflection of human responses than did assays involving a single dose of vaccine.